Fabrication of UV responsive micelles-containing multilayers and their influence on cell adhesion - Zhang, Haolan (2018)
Multilayers incorporated with stimuli-responsive substances by means of layer-by-layer (LbL) self-assembly are much attractive due to the advantages of stimuli-responsiveness and potential applications in different fields. In this study, pyrenemethyl acrylate (PA) was synthesized, and was copolymerized with acrylic acid (AA) to obtain the amphiphilic and photodegradable P(PA-co-AA) polymers with a PA:AA molar ratio of 1.3:3, and an average molecular weight of 6.9 kDa and polydispersity index of 1.04. They formed micelles spontaneously when dispersed in aqueous solution with a size of 27.5 nm in a dry state and 136.6 nm in a wet state. The micelles were readily decomposed to form aggregates as a result of the cleavage of the pyrenemethyl ester bonds under UV-irradiation. UV-responsive micelles-containing multilayers were prepared by LbL self-assembly of the UV-responsive micelles and polyallylamine hydrochloride (PAH). UV-irradiation of the multilayers resulted in the decomposition of micelles, leading to larger surface roughness, and enhanced swelling ratio and wettability of the multilayers. In vitro culture of A549 and HepG2 cells showed significantly better adhesion at 4 h on the UV-illuminated multilayers, whereas the cell proliferation was not affected until 5 d.